Performance of human papillomavirus E6/E7 mRNA assay for primary cervical cancer screening and triage: Population-based screening in China - Zhang, Jing; Yang, Di; Cui, Xiaoli; Liu, Guangcong; Cui, Zhumei; Wang, Chunyan; Piao, Haozhe (Frontiers in Cellular and Infection Microbiology, 2022)
Objective Cervical cancer screening is very important in the prevention and treatment of cervical cancer. In China, the cervical screening strategy needs to be improved. To explore a suitable cervical screening strategy in China, we evaluated the performance of the human papillomavirus (HPV) E6/E7 mRNA (Aptima HPV (AHPV)) assay in primary screening and different triage strategies for women undergoing routine cervical screening. Methods A total of 10,002 women aged 35 to 65 years of age were recruited in Liaoning Province and Qingdao City, China. Specimens were tested by liquid-based cytology (LBC) and the AHPV assay, and women who tested positive on any test were referred for colposcopy. Genotyping was performed on all high-risk HPV (HR-HPV)-positive samples. Test characteristics were calculated based on histological review. Results We identified 109 women with high-grade squamous intraepithelial lesion or worse (HSIL+), including six with cervical cancer. The sensitivity of AHPV was clearly higher than that of LBC (92.7 [95% CI: 87.2, 97.2] vs. 67.9 [95% CI: 59.6, 76.1], p < 0.001). The specificity of AHPV was 93.0 (95% CI: 92.5, 93.5), which was lower than that of LBC (95.2 [95% CI: 94.8, 95.6], p < 0.001). There was no statistical difference between the positive predictive value of AHPV and LBC (13.5 [95% CI: 11.2, 16.2] vs. 14.3 [95% CI: 11.4, 17.6], p = 0.695). The difference of area under the curve (AUC) values between the AHPV test (0.928 [95% CI: 0.904, 0.953]) and LBC test (0.815 [95% CI: 0.771, 0.860]) in detecting HSIL+ was statistically significant (p < 0.001). Finally, among the three triage strategies, both the sensitivity (73.4 [95% CI: 65.1, 81.7]) and AUC (0.851 [95% CI: 0.809, 0.892]) of AHPV genotyping with reflex LBC triage were the greatest. Conclusion In summary, the AHPV assay is both specific and sensitive for detecting HSIL+ and may be suitable for use in primary cervical cancer screening in China. AHPV genotyping with reflex LBC triage may be a feasible triage strategy.